ANALISIS KEPEMIMPINAN PARTISIPATIF DALAM MENINGKATKAN MOTIVASI DAN KINERJA PEGAWAI SEKTOR PUBLIK: KAJIAN LITERATUR - La Ode Muhammad Ichwan Sjachrawy; Maudhy Satyadharma; Muhammad Asrin (Cangkal : Jurnal Ilmu Sosial Dan Humaniora, 2026)
This study aims to analyze participatory leadership in improving the motivation and performance of public sector employees through a literature review approach. The research method uses a literature study with a narrative model through analysis of various scientific journals and relevant sources. The results of the study indicate that participatory leadership plays a significant role in improving motivation, job satisfaction, internal communication, and employee performance through employee involvement in decision-making. However, its effectiveness is influenced by organizational culture, work environment, institutional systems, and employee characteristics. In addition, organizational culture has been shown to contribute significantly to improving the performance of public sector employees. Therefore, the implementation of participatory leadership needs to be supported by a collaborative work culture, open communication, accountability, and sustainable human resource development to improve the quality of public services.